Manajemen risiko rantai pasok garam madura melalui pendekatan RapAgRisk - Solehatun Munawaroh; Novita Erma Kristanti; Wahyu Supartono (AGROINTEK, 2026)
Salt is a strategic commodity that plays an important role in both the food and industrial sectors in Indonesia. However, supply chain actors continue to face various risks that reduce logistics efficiency and compromise product quality, especially in Madura, the main center of national production. This study aims to identify, analyze, and mitigate risks at each tier of the Madura salt supply chain, while assessing the quality of products affected by these risks. The study used the Rapid Agricultural Supply Chain Risk Assessment (RapAgRisk) method, which refers to ISO 31000:2018. Data were collected through field observations and in-depth interviews with 64 respondents consisting of farmers, collectors, wholesalers, and retailers in Sampang and Sumenep Regencies. Risk analysis was conducted using a probability, severity, and capacity to manage risk matrix, while quality analysis focused on moisture and NaCl content. The results of the study showed 17 main types of risks, with the highest risk at the farmer tier being high rainfall and storage in open areas (high expected loss and high vulnerability categories). Quality tests showed that under the risk condition of untimely or early harvesting (R.T.2), the moisture content reached 5.21% and NaCl 92.38%, while under the risk of mud contamination due to geomembrane leakage (R.T.5), the moisture content increased to 8.70% and NaCl decreased to 87.29%. The moisture value under R.T.5 exceeded the SNI threshold of ≤7%, and all samples exposed to risk failed to meet the NaCl requirement of ≥94%, indicating a significant decline in product quality. The proposed mitigation strategies include providing reservoirs to store old water so that it does not mix with water and establishing joint storage institutions, such as cooperatives or warehouse rentals. For collectors and wholesalers, it is recommended to diversify markets and inter-regional price contracts to anticipate price fluctuations and changes in demand patterns. At the retail level, mitigation focuses on improving sanitation and product protection, such as storing salt in closed containers and layered packaging.